Correction: Corrigendum: Structural basis of synaptic vesicle assembly promoted by α-synuclein - Giuliana Fusco (Nature Portfolio, 2017)
Nature Communications 7: Article number: 12563 (2016); Published: 19 September 2016; Updated 11 May 2017 In the original version of Supplementary Data 1 associated with this Article, the FastPeakFind.m function was incorrectly attributed to the authors in the function’s header. This function is Copyright © 2012 Adi Natan, Stanford University (natan@stanford.